Influências precoces sobre o capital humano de adultos jovens: análises dos efeitos do baixo peso ao nascer e de catch-up de altura na coorte de nascimentos de Ribeirão Preto, São Paulo (1978/79) - GARCIA, Paola Trindade (2017)
There is growing evidence that early factors have important influences on human capital in adult life. In this scenario, low birth weight and height catch-up would be important markers for these analyzes, considering the possibilities of influence on schooling and future work conditions, key elements for the accumulation of human capital. This study aimed to determine the effect of low birth weight and height-catch-up on the human capital of young adults from data from one of the country's oldest birth cohorts: the birth cohort of Ribeirão Preto, São Paulo, 1978/79. This is a prospective longitudinal cohort study. The sample consisted of all young adults enrolled in the fourth phase of the cohort, totaling 2,063 individuals (31.8% of the original cohort) for analysis. 1,004 individuals had sufficient information to calculate the catchup height at school age. Two theoretical models were developed, followed by analysis plan based on structural equations (using Mplus 7.31). Exposure variables were low birth weight and catch-up height and the human capital outcome (latent variable composed of three indicator variables: schooling, income and occupation). It was verified that low birth weight exerts a negative direct effect on human capital in adult life (CP = -0.109 / p = 0.018). However, the greatest effect was observed in maternal human capital on adult human capital (CP = 0.671 / p <0.001). The occurrence of catch-up height in school age has a direct and positive effect on human capital in adult life (CP = 0.154 / p = 0.034). In addition, maternal human capital exerts a positive effect on the occurrence of catch-up height at school age (CP = 0.160 / p = 0.012). These results support the set of findings that point to the importance of interventions that prevent the occurrence of underweight as well as those that promote growth recovery adequately, since both strategies will result in substantial gains in key aspects for capital education, work and income.